Expression changes in protein-coding genes and long non-coding RNAs in denatured dermis following thermal injury. Issue 5 (August 2020) - Yu, Wenchang; Guo, Zaiwen; Liang, Pengfei; Jiang, Bimei; Guo, Le; Duan, Mengting; Huang, Xu; Zhang, Pihong; Zhang, Minghua; Ren, Licheng; Zeng, Jizhang; Huang, Xiaoyuan
Highlights: LncRNA LINC00302 was downregulated in thermal injured dermis tissue sample. LINC00302 promoted the human dermis fibroblasts viability. LINC00302 increased α-SMA and Collagen I levels in human dermis fibroblasts viability. Abstract: Objective: Thermal injury repair is a complex process during which maintaining the proliferation of human dermis fibroblasts (HDFs) and synthesis of extracellular matrix (ECM) plays a critical role. In the present study, we analyzed potential molecular markers and the probable association between differentially-expressed lncRNAs and protein-coding genes within denatured dermis following thermal injury, attempting to provide further insights to thermal injury repair pathogenesis. Methods and main results: We found that the expression of 3940 lncRNAs was increased, while that of 1438 lncRNAs was reduced in the denatured dermis following thermal injury when compared to normal tissue. Of them, 338 were upregulated and 154 were downregulated by more than 128 times. Via cross-check with another microarray profile analysis on differentially-expressed lncRNAs after thermal injury, LINC00302 was found to be downregulated after thermal injury; more importantly, this skin-specially expressed lncRNA is located near a series of genes related to multiple skin inflammation and skin barrier-associated genomes. LINC00302 overexpression promoted the cell viability and the protein levels of α-SMA and Collagen I in HDFs. Conclusions: In conclusion, mRNAs and lncRNAs could be differentially expressed in the denatured dermis following thermal injury. mRNA and lncRNA regulatory signaling pathways could participate in thermal injury repair pathogenesis. More importantly, LINC00302 may play a critical role in thermal injury repair.